الاستثمارات السياحية خيار استراتيجي للتنويع الاقتصادي بالجزائر قراءة للواقع والمأمول - بارك نعيمة; بوشناف فايزة; بن داودية وهيبة (My University, 2021)
تهدف هذه الدراسة الى ابراز أهمية الاستثمارات السياحية كخيار استراتيجي للتنويع الاقتصادي التي تعول عليها الدول بصفة عامة والجزائر بصفة خاصة، وتطرقنا الى اهم الجهود المبذولة من طرف الحكومة الجزائرية لتشجيع لاستثمار السياحي، ووقفنا على اهم المعوقات التي تحول دون تحقيق هذه المشاريع على ارض الواقع، وخلصت الدراسة الى انه بالرغم من توفير مجموعة من المتطلبات والحوافز الا انه تبقى قليلة وهذا ما قدمناه في شكل توصيات من أجل ترقية الاستثمارات السياحية بالجزائر. This study aims to highlight the importance of tourism investments as a strategic option for economic diversification, on which countries in general and Algeria in particular depend on them. We have touched upon the most important efforts made by the Algerian government to encourage tourism investment, and we have stopped the most important obstacles that prevent the realization of these projects on the ground. The study indicated that despite providing a set of requirements and incentives, they remain few, and this is what we have presented in the form of recommendations for the promotion of tourism investments in Algeria.